Optimasi Sistem Produksi dan Manajemen Rantai Pasok dalam Mengelola Risiko Pasar pada Industri Daur Ulang Plastik - , Mawardi; Syamsuddin, Nurfiani; , Rahmad; Usman, Bukhari; Syamsuddin, Syafrina; Dida Nurida, Putri (Jurnal Serambi Engineering, 2026)
This study examines the integration of production system optimization, supply chain management, and market risk management in the plastic recycling industry within a circular economy context. Using a qualitative systematic literature review approach covering publications from 2017 to 2025, this study synthesizes findings from Scopus, Web of Science, OECD, and World Bank sources. The results indicate that production optimization strategies such as lean manufacturing, process simplification, energy efficiency, and capacity planning enhance cost efficiency and operational stability. At the same time, effective supply chain management, including reverse logistics coordination, supplier diversification, and inventory control, strengthens supply chain resilience and reduces disruption risks. Cost efficiency and supply stability increase price flexibility, which mitigates market risk exposure and supports profitability stability. The study proposes an integrative conceptual framework linking production optimization, supply chain coordination, market risk mitigation, and profitability resilience. The findings contribute to bridging operations management and risk governance literature while offering practical insights for improving competitiveness and sustainability in the plastic recycling sector.